Peptide profiling of goat milk fermented by Lactobacillus delbrueckii ssp. delbrueckii BD7: Identification of potential biological activity (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rubak YT, Nuraida L, Iswantini D, Prangdimurti E, Sanam MUE. 2021. Peptide profiling of goat milk fermented by Lactobacillus delbrueckii ssp. delbrueckii BD7: Identification of potential biological activity. Biodiversitas 22: 3136-3145. This study investigated the angiotensin-converting enzyme (ACE) inhibitory activity in fermented goat milk by Lactobacillus delbrueckii ssp. delbrueckii BD7, characterizing the peptide and its potential as a bioactive peptide. The starter culture (2%) was inoculated into pasteurized goat skim milk (11%), then incubated at 37 °C until it reached pH 4.6. Centrifugation at 6000 g x 10 minutes at 4 °C was applied. The supernatant obtained was then ultrafiltrated using a membrane cut-off with a molecular weight of 3 kDa, and the fraction obtained was analyzed to determine the inhibitory activity of ACE. Peptides were characterized using Nano LC / MS / MS, and identification as bioactive peptides was carried out based on a literature review. ACE inhibitory activity of fermented goat milk of Lb. delbrueckii ssp. delbrueckii BD7 was 55.98 ± 3.53%. A total of 157 peptides were released with molecular weights ranging from 770.78 - 2081.12 Da and having 7-19 amino acid residues. The main peptide was hydrolyzed from casein (72.6%), cleavage in the parent protein, specific for aliphatic and aromatic amino acids. Identification of bioactive peptides based on the similarity of amino acid residues at C-terminal obtained 28 ACE inhibitor peptides, 19 antioxidant peptides, and ten antimicrobial peptides. Some of these peptides have homologous sequences with previously reported peptides. Lb. delbrueckii ssp. delbrueckii BD7 has the potential as a starter culture to produce fermented milk, which is rich in biological activity.